1998
DOI: 10.1038/sj.onc.1201578
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induces a persistent activation of JNK that is related to cell death

Abstract: Genotoxic stress triggers signalling pathways that either mediate cell killing or protection of a ected cells. While induction of p53 is observed for most of the genotoxins, activation of MAPK/SAPK cascades is not a general response. The role of MAPK/SAPK activation on cell fate, seems to be dependent, in some systems, on the balanced response among both cascades. We have here examined the e ect of cis and trans-DDP on the activation of ERK and JNK activities. While no signi®cant induction of ERK was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
183
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 216 publications
(199 citation statements)
references
References 30 publications
14
183
2
Order By: Relevance
“…In agreement with this latter study, we found differences in sub-cellular distribution of MKP1: mainly cytoplasmic in normal tissue and nuclear in tumor tissue. As the preferred substrate of MKP1 is JNK and this is translocated to the nuclei following a stimulus (Sa´nchez-Pe´rez et al, 1998), it appears reasonable to propose that a preferential distribution of MKP1 to this sub-cellular compartment would be to facilitate its access to the substrate. Furthermore, we found that expression of MKP1 was detected from very early stages in tumor development and maintained until later stages, indicating that it should be advantageous for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In agreement with this latter study, we found differences in sub-cellular distribution of MKP1: mainly cytoplasmic in normal tissue and nuclear in tumor tissue. As the preferred substrate of MKP1 is JNK and this is translocated to the nuclei following a stimulus (Sa´nchez-Pe´rez et al, 1998), it appears reasonable to propose that a preferential distribution of MKP1 to this sub-cellular compartment would be to facilitate its access to the substrate. Furthermore, we found that expression of MKP1 was detected from very early stages in tumor development and maintained until later stages, indicating that it should be advantageous for tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Cell extracts, Western blots and RT-PCR Whole-cell extracts were prepared essentially as described previously (Sa´nchez-Pe´rez et al, 1998). Western blotting was performed using standard methods (Sa´nchez-Pe´rez et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations